2022
DOI: 10.3390/md20070417
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the In Vivo, In Vitro, and In Silico Wound Healing Potential of Pinctada martensii Purified Peptides

Abstract: Previous studies found that both oral and topical administration of enzymatic digestion products < 3 K Da ultrafiltration fractions of Pinctada martensii mantle (PMPs) had pro-healing effects. Thus, we further purified them by Sephadex-G25 and screened them by cellular assays to obtain Pinctada martensii purified peptides (PMPPs). In this study, we explored the mechanism of PMPPs on wound healing by in vivo, in vitro, and in silico experiments. LC-MS/MS results showed that PMPPs consisted of 33 peptides wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This beneficial effect may be attributed to the enhancement of collagen metabolism and fibroblast proliferation. Importantly, our study focused on the activity of natural proteins extracted from PM, as opposed to their enzymatic hydrolysates, which distinguishes it from existing research [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This beneficial effect may be attributed to the enhancement of collagen metabolism and fibroblast proliferation. Importantly, our study focused on the activity of natural proteins extracted from PM, as opposed to their enzymatic hydrolysates, which distinguishes it from existing research [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of mucus is secreted during the growth of PM, which has been made attention to by researchers. Previous studies have shown that enzyme products derived from PM meat and small molecular polypeptides from the mantle have promoted wound healing in rats, with amino acids and various peptides being the main components [ [26] , [27] , [28] , [29] ]. However, most of these studies have predominantly focused on PM peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking (MD) is an efficient and trustworthy computational tool for predicting different binding affinities and modes as well as exploring the mechanisms of ligand binding between various molecules and target proteins. As a valuable tool to determine the mode of binding and strength of ligand–protein interactions, MD is frequently employed in the drug discovery and structural biology of natural products [ 38 , 39 , 40 ]. The interaction between proteins and ligands is also vital to take into account, and the interactions with the lowest binding energy are regarded as more stable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, screening original drugs with functions of speeding up skin wound closure and inhibiting scar formation are essential for patients with tissue defects. In this regard, Zhang et al [ 21 ] prepared the best fraction PMPs-4 (PMPPs) from the ultrafiltration fraction (<3 K Da) of shellfish Pinctada martensii mantle (PMPs) via gel chromatography. Cellular assays proved that PMPPs could promote the proliferation of HSF and HaCaT cells, and in vivo animal experiments indicated that PMPPs could achieve scarless healing by regulating the TGF-β/Smad pathway to inhibit the inflammatory response, accelerate the epithelialization process and regulate the collagen I/III ratio.…”
mentioning
confidence: 99%